2014
DOI: 10.1123/jsep.2013-0245
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Examination of the Relationship Between Perfectionism and Motivational Climate in Dance

Abstract: The present study examined the relationship between dance-related perfectionism and perceptions of motivational climate in dance over time. In doing so, three possibilities were tested: (a) perfectionism affects perceptions of the motivational climate, (b) perceptions of the motivational climate affect perfectionism, and (c) the relationship is reciprocal. Two hundred seventy-one young dancers (M = 14.21 years old, SD = 1.96) from UK Centres for Advanced Training completed questionnaires twice, approximately 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 4 publications
1
21
0
1
Order By: Relevance
“…In the present study, there were far greater between-than within-person differences, supporting general psychology literature that perfectionism is a largely stable personality construct (e.g., Rice & Aldea, 2006). However, recent research indicates that perceptions of the motivational climate as task-involving may heighten dancers' perfectionistic strivings over a six-month time period (Nordin-Bates, Hill, Cumming, Aujla, & Redding, 2014). Future research might consider whether particularly stressful times, such as performance seasons or assessment periods, are associated with increased perfectionism for dance and sport performers, and the potential impact on outcomes such as DEA.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, there were far greater between-than within-person differences, supporting general psychology literature that perfectionism is a largely stable personality construct (e.g., Rice & Aldea, 2006). However, recent research indicates that perceptions of the motivational climate as task-involving may heighten dancers' perfectionistic strivings over a six-month time period (Nordin-Bates, Hill, Cumming, Aujla, & Redding, 2014). Future research might consider whether particularly stressful times, such as performance seasons or assessment periods, are associated with increased perfectionism for dance and sport performers, and the potential impact on outcomes such as DEA.…”
Section: Discussionsupporting
confidence: 83%
“…When reporting high levels of PC, elite junior performers might be biased in the way they perceive their teaching/coaching styles (Appleton et al, 2011; Boone et al, 2014; Nordin-Bates et al, 2014). Activated by aspects of controlling conditions, they are likely to enter a kind of hypervigilant state, driven by emotional stress from their conditional self-worth, which in turn, seems to associate with fear of failure and avoidance motivation (Shafran et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The displaying of higher levels of PC might also function as a substitute for being externally controlled, as a way of taking the control back, directing it into self-control, obsessiveness, and relentless pursuit for success (Shafran et al, 2002; Boone et al, 2014). Thus, such behavior might trigger and increase the PC tendencies within performers, whereas, when faced with low controlling conditions these tendencies might be immobilized (Shafran et al, 2002; Nordin-Bates et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a large number of research investigating sports perfectionism (Dunn, Dunn, & Syrotuik, 2002;Hamidi & Besharat, 2010;Nordin-Bates, Hill, Cumming, Aujla, & Redding, 2014;Sagar & Stoeber, 2009) and perceptions of the trainer behavior (Bortoli, 2015;Gesualdo, 2011;Jurko et al, 2013;Kenow & Williams, 2016). The results of the research conducted by Djurovic, Sokic, and Aleksic-Veljkovic (2017) have shown that, during training and sports performance, the appearance of the non-adaptive protectionist tendencies, manifested in the form of the negative cognitive and emotional reactions, represent the athlete's reaction to imperfections in the performance, and can significantly affect the occurrence of the pathological behaviors (they may cause pathological eating habits).…”
Section: Introductionmentioning
confidence: 99%